DEVELOPMENT OF THE CLIMATE VILLAGE PROGRAM IN TOBEK GODANG SUB-DISTRICT, PEKANBARU CITY AT 2020-2021 - Nurpeni Nurpeni; Aguswan Aguswan; Widia Astuti; trio saputra (Universitas Padjadjaran, 2022)
Development of the climate village program, Tobek Godang Village, Pekanbaru City. This study aims to describe the development of the climate village program as a national program that has been established by the Indonesian Ministry of Environment and Forestry, No. 84 of 2016 concerning Proklim. In its implementation, Tobekgodang Village has implemented a climate village program in its working area. Still, in the performance of its development, there are various obstacles, including government support (related agencies), the Provincial Environment Service (DLKH), and the Pekanbaru City Environment and Cleanliness Service, especially support for the provision of resources which is still low in development of the climate village program (proklim) at the Tobekgodang sub-district level. The research approach uses a qualitative approach by describing development aspects in behavior change, shared vision, and inter-organizational cooperation. The research results that have been achieved are that pro-climate development has been implemented in the Tobek Godang sub-district area. Still, the community’s knowledge, understanding, and participation in the climate village program have not been realized according to the goals and objectives of the desired climate village program. Research recommendations are as follows (1) the need to socialize the Poklim national program to the village community. (2) Budget resources need to be allocated to develop Proklim in the community. (3) Training for individuals and groups of social institutions needs to be provided with environmental change and resilience.